Long-term exposure to microwave radiation provokes cancer growth: evidences from radars and mobile communication systems - Yakymenko, Igor; Sidorik, Evgeniy; Kyrylenko, Sergey; Chekhun, Vasiliy (My University, 2011)
In this review we discuss alarming epidemiological and experimental data on possible carcinogenic effects of long term exposure to low intensity microwave (MW) radiation. A number of reports revealed that under certain conditions the irradiation by low intensity MW can substantially induce cancer progression in humans and in animal models.
Keywords: non-ionizing radiation; tumor; risk assessment; неіонізуюче випромінювання; пухлина; оцінка ризиків; неионизирующее излучение; опухоли; оценка рисков; кафедра екології та екоменеджменту